2006
DOI: 10.1590/s1516-89132006000500005
|View full text |Cite
|
Sign up to set email alerts
|

Sedative and anxiolytic effects of methanolic extract from the leaves of Passiflora actinia

Abstract: Leaves from several

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 15 publications
2
15
0
3
Order By: Relevance
“…The test results reported in this article also confirmed that isoorientin possessed CNS effects. According to the results in this paper and other reports (Lolli et al, 2007;Santos et al, 2006), there is a conjecture that the effects of flavonoids as CNS active substances are related to the dose administered, namely, anxiolytic-like activity at lower dose and sedative-like activity at higher dose are observed.…”
Section: Spontaneous Activity Testsupporting
confidence: 61%
“…The test results reported in this article also confirmed that isoorientin possessed CNS effects. According to the results in this paper and other reports (Lolli et al, 2007;Santos et al, 2006), there is a conjecture that the effects of flavonoids as CNS active substances are related to the dose administered, namely, anxiolytic-like activity at lower dose and sedative-like activity at higher dose are observed.…”
Section: Spontaneous Activity Testsupporting
confidence: 61%
“…Diante disso, sugerese que novos estudos sejam realizados, com objetivo de verifi car a presença dos princípios ativos, na farinha da casca de maracujá, responsáveis pela propriedade sedativa, uma vez que substâncias já foram encontradas em outras partes da planta como folhas, fl ores, caule e polpa dos frutos (Zibadi;Watson, 2004;Yuldasheva et al, 2005;Santos et al, 2006).…”
Section: Discussionunclassified
“…Animal behavior was evaluated using the EPM and open field test as previously described (Santos et al, 2006). Initially, mice were individually placed in the center of the EPM and allowed 5 min of free exploration.…”
Section: Behavioral Testsmentioning
confidence: 99%